Hukum Material Dan Hukum Formal Fiqih Muamalah Dalam Akad Mudharabah Pada Produk Perbankan Syariah Di Indonesia - Sri Wahyuni, Sena; Irfan Akmal Maulana, Muhammad; Tuburpon, Amadia; Azizah, Nurul (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2025)
The mudharabah agreement is a form of cooperation in muamalah fiqh which is widely used in sharia banking products in Indonesia. This contract has two important aspects, namely material law (substance of the agreement) and formal law (implementation procedures). In the context of sharia banking, there are challenges in integrating fiqh principles with national banking regulations, so a more in-depth study is needed regarding the application of these two legal aspects. This research aims to analyze aspects of material law and formal law in mudharabah contracts for sharia banking products in Indonesia. The research method used by researchers is a qualitative descriptive approach. Data was obtained through a study of muamalah fiqh literature, statutory regulations, and sharia banking practice documents. The research results show that in the material legal aspect, mudharabah contracts are generally in accordance with sharia principles. However, in the formal legal aspect, there are still several obstacles, especially in terms of documentation and compliance with formal regulations set by banking authorities. The discussion indicated the need for harmonization between sharia banking regulations and the principles of muamalah fiqh, in order to increase compliance and clarity in the implementation of mudharabah contracts. Keywords: Material Law, Formal Law, Mudharabah Agreement, sharia banking